2013
DOI: 10.1021/ed2007668
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Terminology, Experience, and Energy Concepts in Student Conceptions of Freezing and Boiling

Abstract: A discussion of some student conceptions of the solid–liquid and liquid–vapor phase transitions is presented. Data from open-ended, short-answer questions were collected from first-semester general chemistry students and then discussed in the context of previous studies. The responses gave insight into the various student conceptions about these phase changes. Student misunderstandings were most often related to (i) contextual difficulties with the terms freezing and boiling associated with their lack of exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…First, 11 students gave responses such as "the particles warm up," revealing that some of the students were assigning the observable behavior of the liquid to each individual particle in the liquid, as if one could place a thermometer on a single particle and measure the same temperature change observed for the liquid. Second, four students suggested that the particles underwent a chemical reaction to yield an increase in temperature, reminiscent of the well-documented difficulties students have in distinguishing between phase changes and chemical reactions (Jasien, 2013). While these misconceptions are common, true concept mastery requires that these ideas be revealed and the scaffolding is corrected.…”
Section: Results and Discussion Objective 1 -Relate Kinetic Energy Particle Motion And Thermal Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, 11 students gave responses such as "the particles warm up," revealing that some of the students were assigning the observable behavior of the liquid to each individual particle in the liquid, as if one could place a thermometer on a single particle and measure the same temperature change observed for the liquid. Second, four students suggested that the particles underwent a chemical reaction to yield an increase in temperature, reminiscent of the well-documented difficulties students have in distinguishing between phase changes and chemical reactions (Jasien, 2013). While these misconceptions are common, true concept mastery requires that these ideas be revealed and the scaffolding is corrected.…”
Section: Results and Discussion Objective 1 -Relate Kinetic Energy Particle Motion And Thermal Expansionmentioning
confidence: 99%
“…Some student misconceptions are concept-specific. For instance, chemistry learners frequently struggle to distinguish phase changes from chemical reactions, which imply that students may have a specific understanding of the states of matter while lacking unifying conceptual knowledge relevant to chemical bonding and noncovalent interactions (Jasien, 2013). More broad chemical misunderstandings are evidenced by students' difficulty relating concepts taught in different courses and even different lessons.…”
Section: Introductionmentioning
confidence: 99%
“…This journal is © The Royal Society of Chemistry 2015 virtually no experience with other liquids. However, as has been noted by Jasien (2013) and Kind (2004), this can be problematic for more advanced students. Therefore, it is essential to develop functional examples for other liquids for them.…”
mentioning
confidence: 89%
“…The reason is that students often equate "intermolecular forces" with "chemical bonds" (Miller, 2016). It is also been observed that because of their lack of experience with other liquids, students often only think of water when they think of phase transitions (Jasien, 2013). Since the predominant intermolecular force holding water molecules together in the liquid is hydrogen bonding, choosing: "(e) Chemical bonds are being broken."…”
Section: Energy Change Questionsmentioning
confidence: 99%